Recent Functionalizations of Primary Sulfonamides - Chen, Yantao (Synthesis, 2016)
Sulfonamides are common building blocks in organic synthesis. They have a wide range of medical applications. This review aims to delineate recent efforts towards the functionalization of primary sulfonamides during last three years and to provide an overview of the synthesis of N-alkylated, N-acylated, and N-arylated sulfonamides from primary sulfonamides. Among other reactions, the sulfonamide-directed C–H functionalization is highlighted. 1 Application of Sulfonamides2 Synthesis of N-Alkylated Sulfonamides3 Synthesis of N-Acylated Sulfonamides4 Synthesis of N-Arylated Sulfonamides5 Other Chemistry6 Summary and Perspective
Keywords: sulfonamides; alkylation; acylation; arylation; C–H functionalization; amidation; directing group; ring closure